Αξιοποίηση των κοινωνικών μέσων δικτύωσης για την δημιουργία δεδομένων εκπαίδευσης: Η περίπτωση της εικόνας στο Instagram - Δημητριάδη, Νικολέττα (Department of Communication and Internet Studies, Faculty of Communication and Media Studies, Cyprus University of Technology, 2015)
This dissertation studies the hashtags given to Instagram in relation to the visual content of the images in order to use them to create training data for machine learning algorithms.
Keywords: Instagram; Hashtags; Αυτόματη επισημείωση εικόνας; Mηχανική μάθηση